The Hsp90 chaperone machinery: Conformational dynamics and regulation by co-chaperones - Li, Jing; Soroka, Joanna; Buchner, Johannes (Biochimica et biophysica acta, 2012)
Hsp90 is a dimeric molecular chaperone required for the activation and stabilization of numerous client proteins many of which are involved in essential cellular processes like signal transduction pathways. This activation process is regulated by ATP-induced large conformational changes, co-chaperones and posttranslational modifications. For some co-chaperones, a detailed picture on their structures and functions exists, for others their contributions to the Hsp90 system is still unclear. Recent progress on the conformational dynamics of Hsp90 and how co-chaperones affect the Hsp90 chaperone cycle significantly increased our understanding of the gearings of this complex molecular machinery. This article is part of a Special Issue entitled: Heat Shock Protein 90 (Hsp90). ► Hsp90 is a complex molecular chaperone machine. ► During the ATPase cycle Hsp90 undergoes large conformational changes. ► Hsp90 is subject to several posttranslational modifications that modify its function. ► Eukaryotic Hsp90 associates with a large cohort of co-chaperones. ► Co-chaperones drive Hsp90-client protein interactions.